BarcodeTree: Scalable Comparison of Multiple Hierarchies - Guozheng Li; Yu Zhang; Yu Dong; Jie Liang; Jinson Zhang; Jinsong Wang; Michael J. McGuffin; Xiaoru Yuan (IEEE Transactions on Visualization and Computer Graphics, 2020)
We propose BarcodeTree (BCT), a novel visualization technique for comparing topological structures and node attribute values of multiple trees. BCT can provide an overview of one hundred shallow and stable trees simultaneously, without aggregating individual nodes. Each BCT is shown within a single row using a style similar to a barcode, allowing trees to be stacked vertically with matching nodes aligned horizontally to ease comparison and maintain space efficiency. We design several visual cues and interactive techniques to help users understand the topological structure and compare trees. In an experiment comparing two variants of BCT with icicle plots, the results suggest that BCTs make it easier to visually compare trees by reducing the vertical distance between different trees. We also present two case studies involving a dataset of hundreds of trees to demonstrate BCT's utility.